COMPARISON OF HYDRODISSECTION INJECTION THERAPY USING ULTRASONOGRAPHIC AS GUIDES BETWEEN TRIAMCINOLONE ACETONIDE AND 5% DEXTROSE IN CARPAL TUNNEL SYNDROME - Widodo Mardi Santoso; Ika Sedar Wasis Sasono; Catur Ari Setianto; Nuretha Hevy (Journal of Pain, Headache and Vertigo, 2022)
Background: Carpal Tunnel Syndrome (CTS) is a symptomatic compression neuropathy of the median nerve characterized by increased pressure in the carpal tunnel and decreased nerve function due to compression of the median nerve in the carpal tunnel. The purpose of the hydrodissection injection method in CTS is to separate the soft tissue adhesions that cause nerve compression and this method are known for being minimally invasive, fast healing, and easy to apply. Local injection of triamcinolone acetonide (TCA) is often used as therapy for CTS because it stabilizes the sodium channels and reduces abnormal stimulatio, thus it relieved the pain. 5% dextrose injection (D5W) is also widely used as therapy of CTS because it is harmless to nerves and may reduce neurogenic inflammation through inhibition of capsaicin-sensitive receptors. Aim: To compare the effectivity of hydrodissection injection therapy using ultrasound guidance with triamcinolone acetonide and 5% dextrose in CTS. Methods: This study recruited 30 participants who diagnosed with CTS and met the inclusion criteria. Participants were divided into two treatment groups, the first group (n=15) was given 1ml TCA injection and 1 ml lidocaine 2%, while the second group (n=15) was given 5% 5 ml Dextrose injection. The parameters measured in this study were NRS, FSS, and SSS value before injection and 4 weeks after injection of the agent. We compared these parameters at week four after injection between the TCA group and the D5W group. Results: NRS values before and 4 weeks after TCA injection (sig 0.001; p <0.05), FSS values (sig 0.020; p <0.05), and SSS values (sig 0.001; p <0.05). NRS before and 4 weeks after injection of D5W (sig 0.002; p <0.05), FSS (sig 0.001; p <0.05), and SSS (sig 0.000; p <0.05). Comparison between TCA injection and D5W injection at 4 weeks after the injection showed that the results was significantly different on NRS (sig 0.806; p> 0.05) for FSS (sig 0.512; p> 0.05) and SSS (sig 0.293; p> 0.05). Conclusion: There is a significant difference in NRS, FSS and SSS values at 4 weeks after hydrodissection injection, using either TCA or D5W. TCA hydrodissection injection compared to D5W hydrodissection injection was equally effective in improving NRS, FSS and SSS after 4 weeks of injection.